INTEGRASI PEMBELAJARAN MADRASAH DINIYAH TAKMILIYAH KE SEKOLAH (Studi Kasus di Sekolah Dasar Negeri Cisaat Kabupaten Sukabumi) - Juju Saepudin (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
This article presented the results of research on the Integration of Learning Madrasah Diniyah Takmiliyah (MDT) to Schools. This research was motivated by the existence of such as fierce controversy among the public regarding the enactment regulation of Minister of Education and Culture Regulation Number. 23 of 2017 concerned School Day. The study was a case study conducted at the Cisaat State Primary School (SDN) Sukabumi District, West Java Province. Data collection techniques combine field observations, in-depth interviews and documentation studies. Inductive data analysis yields some conclusions as follows: first, the integration of MDT learning in Cisaat Elementary School is done through an integrative and collaborative model. Second, the integration model of MDT learning in the new Cisaat Elementary School in the form of curriculum content and empowerment of some MDT teachers, not in the form of learning facilities or facilities. Third, the motivation of MDT managers, the spirit of the Diniyah Takmilyah Communication Forum (FKDT) board, and the existence of Regional Regulations (Perda) and Regent Regulations (Perbup) are supporting factors for the integration of learning. Whereas the limitations of facilities and infrastructure as well as the absence of special MDT supervisors have an effect on the implementation of learning on MDT to be less professional.